MODEL PEMBELAJARAN BCCT MELALUI SENTRA SENI UNTUK MENGEMBANGKAN KREATIVITAS ANAK USIA 5-6 TAHUN DI TK ISLAMIYAH - Puteri, Sylvana; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research focused on BCCT learning model through art center to develop creativity of 5-6 year old child of Islamiyah Kindergarten. A common problem in this study is "How does the BCCT learning model through art centers to develop creativity in children aged 5-6 years in Islamiyah Kindergarten?". The method used in this research is descriptive and using qualitative research approach. The technique used in this research is triangulation with data gathering tool that is interview guides, observation guidance and documentation. The subject of the research is the teacher of art center and children aged 5-6 years in Islamiyah. The result of the research concludes that the planning, implementation and evaluation of BCCT learning model through art center in developing creativity of children aged 5-6 years is implemented using four steps namely environmental structuring, scaffolding before play, scaffolding during play, and scaffolding after playing. Suggestion from researcher, that is: (1) Teachers can make own props and media of play by utilizing natural materials, waste and traces in overcoming the limitations of the props (2) Teachers can see the reference in the arrangement of the main environment by doing wise spatial arrangement 3) The need for maintenance of play materials that have been available.Keyword: BCCT Learning Model, Art Center, Creativity